TEKNIK ANALISIS NASKAH BERHURUF ARAB - Masyhudi (Berkala Arkeologi, 2000)
Analysis of Arabic-lettered manuscripts is a research process that requires accuracy and care, for this reason it is necessary to have support from various disciplines to be able to help solve the problems that exist in the manuscript. So that what has become the research objectives can actually be achieved. In connection with this, of course in a study it is necessary to have methods and techniques that are truly accurate and clear. There are several stages that must be passed, this is intended to achieve a truly focused analysis. In addition, specifically in the process of analyzing Arabic-lettered manuscripts, there are things that really need to be considered, including things that are closely related to Arabic letters and language, including the supporting sciences. This is intended to prevent errors, so that in the end it can provide a clear and accurate interpretation.